Aligning IT strategy with business strategy for competitive advantage: a structural equation model. (1st January 2013) - Abdi Mussa, Mohammed; Dominic, P.D.D.; Downe, Alan Giffen; Loke, Siew-Phaik; Thamaraiselvan, N.
For the last two decades, Information Technology (IT) in general, and information systems (IS) in particular have rapidly advanced in capability and have changed the way organisations do business. For many firms, IT spending constitutes one of the largest yearly budget items. Alignment IT strategy and business strategy has assumed significant importance in business planning. However, the factors influencing strategic alignment and its effect on the competitive advantage of firms have remained understudies. The objectives of this research were to identify the behavioural, technical and organisational factors underlying strategic alignment and to investigate strategic alignment influence on the use of IT for competitive advantage. A questionnaire was administered to 202 IT and business executives in the Malaysian tour and travel agencies. Data were analysed using structural equation modelling (SEM) techniques to validate a hypothesised second-order model of strategic alignment model. Analysis supported the hypothesis that the alignment of IT strategy with business strategy has a positive influence on the use of IT for competitive advantage.